ChemInform Abstract: Selective Radical Amination of Aldehydic C(sp2)—H Bonds with Fluoroaryl Azides via Co(II)‐Based Metalloradical Catalysis: Synthesis of N‐Fluoroaryl Amides from Aldehydes under Neutral and Nonoxidative Conditions. Issue 43 (21st October 2014) - Jin, Li‐Mei; Lu, Hongjian; Cui, Yuan; Lizardi, Christopher L.; Arzua, Thiago N.; Wojtas, Lukasz; Cui, Xin; Zhang, X. Peter
Abstract This approach represents the first example of aldehydic C—H amination with aryl azides.